PERANAN MEDIA PEMBELAJARAN DALAM KURIKULUM 2013 - Hari Sugiharto Setyaedhi (Universitas Negeri Surabaya, 2021)
The curriculum aims to prepare the 2013 Indonesian man to have the ability to live as individuals and citizens who believe, productive, creative, innovative, and affective and able to contribute to the society, nation, state, and world civilization. A professional teacher is not only required to master the learning material that will be delivered to their students, but also to be able to develop and utilize media and learning resources for the learning process. Media and learning resources is an integral part of the whole process of education in all programs and levels, so the skills to develop and utilize instructional media sorely needed by a professional teacher. The role of media in learning the curriculum in 2013 is very important, because the learning process begins with the activity observed (Reading, listening, listening, seeing (with or without tools). The smoothness and effectiveness of learning, among others, supported by the presence of tools / media / learning resources available. Availability of tools / media / learning resources enable students to learn better, more intensive, and more potential that can be developed. Therefore, tools / media / learning resources need to be presented appropriately in the curriculum of 2013.